Jurisdictions with lowest effective tax rates in the post-BEPS landscape: CbCR evidence and implications - Petr Procházka (European Financial and Accounting Journal, 2020)
The research revolves around the topic of offshore destinations and role of tax in the decision where to locate TNCs' investments or relocate employees. This paper exploits rich country-by-country reporting (CbCR) data that banking institutions operating in the EU with annual turnover over 750 million are obliged to provide publicly as of 2014 on a yearly basis. Database includes 47 banks over 5 years and 27,533 datapoints. I explore whether there is any connection between effective tax rate (ETR) and number of employees in respective subsidiaries of banking institutions. In consequent multiple regression analysis, I add more variables to the model: such as profitability, labour productivity, and other controlling variables. Conclusion is that there is no significant correlation between ETR and employee count and that TNCs tend to locate their employees on a different basis. This is a unique analysis of data that can be used by other tax avoidance researchers and policy makers.
Keywords: F38; H25; H26; 650; Effective tax rate; International tax optimisation; Global mobility; Offshoring; FDI